A study on the awareness of copyright towards digital content among users PTAR, UiTM Puncak Perdana / Hazlin Ibrahim Khan - Ibrahim Khan, Hazlin (2015)
The advent of digital libraries today has been mired with several aspect including the development of appropriate technologies, issues related to storage, right management and so on. With the application of technologies in digital libraries, process of digitization can easily done, the increasing of storage capacity and the improving quality of accessing the materials or information. However, just as digital technology creates new opportunities for library user to have convenient access to massive library digital content, this technology at the same time helps open the possibility of user’s problematic behaviour, such as massive downloading or even copyright law violation. The purpose of this study is to identify on the awareness of copyright and investigate the factor that contribute to the awareness of copyright towards digital content among users PTAR, UiTM Puncak Perdana. To achieve the research objective, quantitative method were use to get the feedback from respondent. Overall, 256 respondent involve in answering questionnaire, then analysed using SPSS software to show the possible correlation between dependent and independent variables selected in study. In addition, SPSS is the most common methods used in order to analyse findings for quantitative data.From the findings, it shows that three factors have a major/significant influence on the awareness on copyright towards digital collection namely policy guidance, promotional programs and training. Finding also shows that three factors discussed in this study have a relationship and contribute to the lawful attitude of respondent. In general, the findings can conclude that for PTAR, UiTM Puncak Perdana users, there is evidence that policy guidance, promotional activities and training about copyright is related to lawful attitude. In particular,it indicate that the more a user knows about copyright, the greater their lawful attitude when accessing the digital content provided by library. However, the importance of respecting intellectual property rights in particular copyright on digital content is still at a moderate level. In spite the fact that most respondents agree with the importance of copyright, yet a high percentage of them indicate that they still use paragraphs from published articles with certain reasons. Therefore, it is necessary for those who involved with the digital content creation to be well conversant with copyright issues, educate and make the library users aware in how to respect others intellectual property. It is important to avoid any copyright infringement due to the awareness and understanding of user towards copyright.The outcomes of the study will form the basis for awareness-raising in supporting of the institutional of systems that facilitate the protection and easy access to learning materials. Hence, the results can be used as a guide to the improvement of library services, especially in terms of digital content. There is a need to protect property rights yet allow creative use of content by university communities in UiTM. As a further extension to this study, it would be interesting to see the future research engage with respondents from different background and different faculty, then in other Academic Libraries in Malaysia. In addition, researcher suggests that in the future research, the qualitative and mix approach is being used to collect and gathered the data to achieve research objectives